Integrated IT project management : a model-centric approach - Bainey, Kenneth R. (Artech House effective project management series., 2004)
Annotation "Integrated IT Project Management: A Model-Centric Approach utilizes practical applications of real-world policies, roles and responsibilities, templates, process flows, and checklists for each of these three component processes. It shows how such processes ensure optimum utilization of people, process, and technology resources during the management and delivery of IT projects. The book provides insight into the key components of the Rational Unified Process from IBM Rational Corporation and the Project Management Body of knowledge PMBOK from the Project Management Institute (PMI) illustrating how they work together and align based on industry processing standards."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.